IMPLEMENTASI KURIKULUM MERDEKA BELAJAR TERHADAP PERUBAHAN ASPEK KOGNITIF SISWA DI SD 01 MUHAMMADIYAH LIMBOTO - Rahmi R Musa; Said Subhan Posangi; Rinaldi Datunsolang (Al-mujahidah, 2026)
This study aims to analyze the implementation of the Merdeka Belajar curriculum on the cognitive aspects of students at SD 01 Muhammadiyah Limboto. The research approach used was a qualitative case study method, where data were obtained through interviews, observations, and documentation. The results of this study indicate that the implementation of the Merdeka Belajar curriculum has a positive impact on students' cognitive development, as seen in the improvement of critical, analytical, and creative thinking skills. Teachers act as facilitators who assist students in the learning process through active methods, project-based learning, and continuous assessment. In addition, learning planning is carried out systematically through the preparation of learning outcomes, learning objectives, and teaching modules. The involvement of teachers and students also strengthens the effectiveness of curriculum implementation. Thus, the implementation of the Merdeka Belajar curriculum is proven to be able to significantly improve students' cognitive aspects and become an educational innovation relevant to the needs of the times.